Octahedral Oxo-Bridged Tri-Nickel(II) Complex with 1,3,5-Tris(2-hydroxyphenyl)-2,4-diazapenta-1,3-diene - Daniil R. Bazanov; Egor D. Korolyov; Konstantin A. Lyssenko; Natalia A. Lozinskaya (Molbank)
An octahedral nickel(II) complex of 1,3,5-tris(2-hydroxyphenyl)-2,4-diazapenta-1,3-diene was obtained and characterized by X-ray crystallography. The organic ligand was obtained by the reaction of 2-hydroxybenzaldehyde with aqueous ammonia solution.